Penerapan Metode Market Basket Analysis (MBA) dengan Algoritma Apriori Untuk Menganalisis Pembelian Jajanan Khas Lebaran Pada Warung Sembako di Toko Win - Nugraheni, Wahyu; Nugroho, Adi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Market Basket Analysis is determining marketing strategies to meet products that will be purchased simultaneously by consumers who are frequently used and most useful for marketing environments that apply an "if-then" pattern. The aim is to identify which can be used as a reference in determining the layout of items with a combination of items that are frequently purchased and interconnected in order to increase sales with the right marketing strategy Research was conducted at the Win Store where so far there is a lot of data accumulate that is only used as archives or bookkeeping, so as to help increase sales by making sales transaction data as new information by processing it using the Basket Analysis Method and the Apriori Algorithm using Rapid Miner Studio.Here using 7 data atribut namely Astor, Kastangel, Spinach Chips, Seblak Chips, Intestine Chips, Monde, and Nastar, and 50 data records, with a minimum support limit = 0.4 and minimum confidence = 0.6 which produces 14 rules. And the highest item set combination pattern obtained in this study is [NASTAR, MONDE] => [KASTANGEL] yielding a confidence of 85.7%.